Statement of Peer Review - Umberto Galietti; Gabriele Arcidiacono; Enrico Armentani; Davide Castagnetti; Vigilio Fontanari; Aurelio Somà; Nicola Bonora (Engineering Proceedings, 2025)
In submitting conference proceedings to Engineering Proceedings, the Volume Editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review, administered by the Volume Editors [...]